STUDY ON THE RIGIDITY OF THE TRUCK SCALE BODY BASED ON THE PRESTRESSED-TREATMENT METHOD - WEI TiePing; YANG XiaoXiang; XU YiQing; YAO JinHui (Jixie qiangdu)
Excessive deflection of the truck scale body is a primary cause leading to measurement error. The prestressedtreatment method of steel structure was applied to the welding procedure of the truck scale body and U-beam. The mathematical relationship model between the preload and the deflection and stress of the truck scale body was constructed. In addition,the prestressed-treatment process was carried out based on finite element method. The results show the deflection of the simulation results is consistent with the changing rule of the mathematical model. Therefore,the deflection of the truck scale body can be improved effectively with the prestressed-treatment method of steel structure,which can be able to improve its measuring accuracy.